The Effect Of Firm Size And Total Assets Turnover (Tato) On Firm Value Mediated By Profitability In Wholesale And Retail Sector Companies - Mario Hasangapon; Deni Iskandar; Eka Desy Purnama; Lambok DR Tampubolon (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
This research is a quantitative study from financial reports of wholesale and retail companies from 2016 to 2019 which are listed in Indonesia Stock Exchange, which aim to find out: 1) The effect of Firm Size on Firm Value (2) The effect of Total Asset Turnover (TATO) against Firm Value, (3) The effect of Profitability on Firm Value, (4) The effect of Firm Size on Profitability, (5) The effect of Total Asset Turnover (TATO) on Profitability as mediator and (7) The effect of Total Asset Turnover (TATO) on Firm Value with Profitability as mediation. The company’s management will provide good performance which can be observed from the financial reports. This will give signals to the investors that the company is in good condition so that the investors are willing to invest their funds in that company. The samples from this study is trading companies consisting of 47 wholesale companies and 15 retail companies in which 15 companies are matched with the criteria. The sample selection technique used is purposive sampling to obtain 15 out of 57 companies matched with the criteria to be tested. This study used a multiple linear regression analysis techniques using SPSS 25. The data analysis technique used in this study is the classical assumption test including the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The data analysis used to test the hypothesis is the f test and t test and path analysis to test the mediation of profitability. In the variable of firm size, TATO and profitability on firm value, have a determinant value R2 of .313, on the other hand, the variable firm size and TATO on profitability has a determinant value of R2 of .074. In conclusion, (1) The size of a company has no significant effect on Firm Value with the Sig. result .317 (2) TATO has a significant positive effect on Firm Value with Sig. result .000 (3) Profitability has a positive significant effect on Firm Value with Sig. ROA .007 (4) The firm size has a significant positive effect on probability with value Sig. result .012 (5) TATO has no significant effect on Probability with Sig. result .0480 (6) Profitability is able to mediate firm size on firm value (7) Profitability is unable to mediate TATO on firm value.